Aplikasi Representasi Real Time Gelombang Electrocardiograph Diskrit (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
This research makes a method to represent in real time the duration of the wave of each cycle of the electrocardiograph record (hereinafter abbreviated EKG) discrete data. Wave data in the form of graphic results, processed through digital signal processing so that the wave results obtained in the form of discrete data and can be processed back into graph data. The duration of time between peak R to peak R is used as the time period of each cycle. The half-step backward shift of HR is the wave end of the previous cycle in the form of an app display so anyone can apply and view virgin medical records in real time with discrete data input data. Discrete data from MIT-BIH and self-measurement results are used as data to obtain the number of cycles in the ECG recording, the R position of each cycle, the duration of each cycle, and the heart rate by using the MATLAB software application. The result of research is the recording data of EKG result that is stored no longer in the form of picture but discrete data, which can be displayed in real time.